IMPLEMENTASI ALGORITMA RC4+ PADA KEAMANAN SISTEM KOMUNIKASI CHATTING PADA WEBSITE SAHEB - Kumala, jericho; Zaman, Baizul; Bahri, Syamsul (KHARISMA Tech, 2025)
Data security in online communication is a crucial issue, especially in applications that handle sensitive information such as SAHEB, which stores users' private chat data in a Firebase database in the Cloud. This study aims to implement the RC4+ 256-bit algorithm on SAHEB application user data to enhance data security. The RC4+ algorithm was chosen for its improved security and efficiency over the RC4 algorithm. Data was collected through observation and creation of 10 dummy chat data sets on the SAHEB web app, simulating user data. The implementation of the RC4+ algorithm was conducted using JavaScript. The study results show that the user chat data was successfully encrypted and decrypted, with an average encryption time of 0.30 ms and an average decryption time of 0.19 ms. Additionally, the Avalanche Effect produced was 3.009%, demonstrating the algorithm's effectiveness in maintaining data integrity.